A Theoretical Overview of Alternative Economic Indicators MEW and ISEW - Varga, József; Bánkuti, Gyöngyi; Csuvár, Ádám; Sebestyénné Szép, Tekla (Acta Scientiarum Socialium, 2019)
In our publication we focus on the economic well-being indicators that can be good substitutes or alternatives of the gross domestic product. After the brief overview of the often mentioned weaknesses and mistakes of GDP, we present the Measure of Economic Welfare (MEW) and the Index of Sustainable Economic Welfare (ISEW). We summarize that albeit there are more than enough indicators, none of them is so widely accepted as GDP. It is not clear yet which one(s) will replace it in its role. The study was created for the Economics Seminar of Kaposvár (KAKTUSZ) which is organized annually by the Kaposvár University. Another research team of the environmental economics session of KAKTUSZ 2016 undertakes to demonstrate other alternative economic indicators in the article titled "Theoretical overview of the GPI, the SNBI and the HDI alternative economic indicators" by Csuvár et al. (2018).